Studi Fenomenologi: Mental Accounting Dalam Investasi Fixed Assets Pada Petani Sawit - Angkawijaya, Riky; Ikhsan, Syarbini; Rusmita , Sari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to understand how oil palm smallholders apply mental accounting in investment decisions on fixed assets, such as the purchase of heavy equipment, operational vehicles, and additional land. The approach used is qualitative with phenomenological methods to explore the subjective experience of oil palm farmers in managing and allocating financial resources. The results showed that farmers unconsciously divided funds into different "mental accounts", such as accounts for family needs, daily operating expenses, and special accounts for long-term investments. This division greatly influences their risk-taking preferences, especially when it comes to fixed asset investment decisions. This study contributes to the understanding of financial behavior in the agricultural sector and is relevant in the development of behavior-based financial assistance strategies.